Crystal structure of bis[trans-(ethane-1,2-diamine-κ(2) N,N′)bis(thiocyanato-κN)chromium(III)] tetrachloridozincate from synchrotron data - Moon, Dohyun (Acta Crystallogr E Crystallogr Commun, 2015)
The structure of the title compound, [Cr(NCS)(2)(C(2)H(8)N(2))(2)](2)[ZnCl(4)], has been determined from synchrotron data. In the asymmetric unit, there are four independent halves of the Cr(III) complex cations, each of which lies on an inversion centre, and one tetrachloridozincate anion in a general position. The Cr(III) atoms are coordinated by the four N atoms of two ethane-1,2-diamine (en) ligands in the equatorial plane and two N-bound NCS(−) anions in a trans arrangement, displaying a slightly distorted octahedral geometry with crystallographic inversion symmetry. The Cr—N(en) and Cr—N(NCS) bond lengths range from 2.0653 (10) to 2.0837 (10) Å and from 1.9811 (10) to 1.9890 (10) Å, respectively. The five-membered metalla-rings are in stable gauche conformations. The [ZnCl(4)](2−) anion has a distorted tetrahedral geometry. The crystal structure is stabilized by intermolecular hydrogen bonds involving the en NH(2) or CH(2) groups as donors and chloride ligands of the anion and S atoms of NCS(−) ligands as acceptors.